2006
DOI: 10.1037/0278-6133.25.5.653
|View full text |Cite
|
Sign up to set email alerts
|

How does optimism suppress immunity? Evaluation of three affective pathways.

Abstract: Studies have linked optimism to poorer immunity during difficult stressors. In the present report, when first-year law students (N = 46) relocated to attend law school, reducing conflict among curricular and extracurricular goals, optimism predicted larger delayed type hypersensitivity responses, indicating more robust in vivo cellular immunity. However, when students did not relocate, increasing goal conflict, optimism predicted smaller responses. Although this effect has been attributed to negative affect wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 36 publications
4
41
0
7
Order By: Relevance
“…Milam et al [23], on the other hand, found that high levels of optimism do not confer any clinical improvement to AIDS patients, although moderate levels were found to be associated with more efficacious immune systems. Segerstrom [24,25] examined two hypotheses that may explain these results: the disappointment hypothesis, according to which persistent and uncontrollable stressors reduce the positive expectations that are typical of optimists and thus consequently control over the stress factors, leading to decrease in immune defence. The other is the engagement hypothesis theorizing that more optimistic individuals are more easily drawn to trying to resolve a problem while pessimists tend to let the matter drop, thus ending up more exposed to stress.…”
Section: Optimism and Physical Healthmentioning
confidence: 99%
“…Milam et al [23], on the other hand, found that high levels of optimism do not confer any clinical improvement to AIDS patients, although moderate levels were found to be associated with more efficacious immune systems. Segerstrom [24,25] examined two hypotheses that may explain these results: the disappointment hypothesis, according to which persistent and uncontrollable stressors reduce the positive expectations that are typical of optimists and thus consequently control over the stress factors, leading to decrease in immune defence. The other is the engagement hypothesis theorizing that more optimistic individuals are more easily drawn to trying to resolve a problem while pessimists tend to let the matter drop, thus ending up more exposed to stress.…”
Section: Optimism and Physical Healthmentioning
confidence: 99%
“…Under the more difficult circumstance, optimism (as measured by the Life Orientation Test-Revised) was negatively associated with delayed-type hypersensitivity responses, a measure of immune responsiveness in the skin. This relationship was not due to the effects of stress as reflected in, for example, negative mood (Segerstrom, 2006). The other possibility is that energetic demands of coping with difficult stressors are greater among optimists, who are more likely to use active than passive coping strategies, both cognitive and behavioral (Solberg Nes & Segerstrom, 2006).…”
Section: Optimism and Immunosuppressionmentioning
confidence: 99%
“…However, the proportion having to do with spending time with others (e.g., "make time for friends and family") was markedly higher among resident students (42% vs. 17% for relocated). These descriptive data suggest that being resident was, in fact, associated with more social goals and obligations having to do with spending time with others (cf., Segerstrom, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…The DTH skin test provides an in vivo assessment of cellular (Th1) immune responses, such that larger indurations reflect more robust cellular immunity. Further analyses then tested whether negative affect could mediate between social network parameters and DTH (c.f., Segerstrom, 2006). If stress contaminates social relationships, then one would expect negative affect to mediate any inverse relationship between social connectedness and immunity; however, if stress results in ecological immunosuppression in order to maintain relationships, mediation by negative affect is less likely.…”
mentioning
confidence: 99%